Mechanical and microstructural changes of cheese cracker dough during baking. (December 2017) - Chong, H.M.; Mohammed, I.K.; Linter, B.; Allen, R.; Charalambides, M.N.
Abstract: Baked food snacks constitute an important market as a popular consumer product. The mechanical properties of cheese cracker dough at different stages of baking have been investigated as they can relate to the product's texture. The change in mechanical properties during baking was measured whilst the corresponding changes in microstructure were recorded using cryo-SEM at several interrupted baking conditions. The initial modulus of the dough increased with baking time due to starch melting or gelatinisation, melting of fat globules and evaporation of water. Simultaneously gas cells were found to begin forming. The data derived from the uniaxial compression, tension and shear experiments showed that the dough exhibited a rate dependent behaviour at all stages of baking with a power law index of approximately 0.2. Rheometric tests under dynamic heating conditions were also performed and it was found that the modulus decreased significantly, from 150 kPa to 10 kPa, with the initial rise in temperature. This study provides useful data for understanding the evolution of microstructure and rheology during the baking process and its impact on the texture of the final product. Highlights: Mechanical and rheological properties of cheese-dough changed with baking time. The material properties were linked to the microstructure observed with cryo-SEM. Rate-dependent deformation behaviour was shown at all stages of baking. The baking temperature and change in microstructure influence the mechanical response.